2002
DOI: 10.1021/jf011072s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid Fraction, Emulsifier Fraction, and Mean Particle Diameter of Oil-in-Water Emulsions on the Release of 20 Aroma Compounds

Abstract: The influence of compositional and structural properties of oil-in-water emulsions on aroma release was examined under mouth conditions. The lipid (0.40 and 0.65) and emulsifier fractions (0.007, 0.010, and 0.014) were varied, as well as the mean particle diameter of the dispersed phase (0.60, 0.73, 0.85, and 1.10 microm). Aroma compounds were isolated in a model mouth system and quantified by gas chromatography-mass spectrometry. Studies were carried out to separate effects on the thermodynamic and the kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 21 publications
(33 reference statements)
4
57
1
Order By: Relevance
“…No influence of a possible enrichment of flavour molecules at the interfacial membrane 27 was established. These results are in agreement with the work by van Ruth et al 15 and are explained by a constant fluctuation of emulsifier molecules at the interfacial area between emulsifier molecules at the droplet surface, molecules dissolved in the aqueous phase and micellar aggregates. 28 The results also suggest that volatiles sensitive to temperature and pressure do not necessarily have to be added before homogenisation, pasteurisation or sterilisation (eg flavoured milk), but can also be added afterwards.…”
Section: Effect Of Emulsifiersupporting
confidence: 93%
See 2 more Smart Citations
“…No influence of a possible enrichment of flavour molecules at the interfacial membrane 27 was established. These results are in agreement with the work by van Ruth et al 15 and are explained by a constant fluctuation of emulsifier molecules at the interfacial area between emulsifier molecules at the droplet surface, molecules dissolved in the aqueous phase and micellar aggregates. 28 The results also suggest that volatiles sensitive to temperature and pressure do not necessarily have to be added before homogenisation, pasteurisation or sterilisation (eg flavoured milk), but can also be added afterwards.…”
Section: Effect Of Emulsifiersupporting
confidence: 93%
“…Static headspace studies showed that O/W emulsions with decreased oil droplet diameters resulted in increased flavour release in the case of non-polar compounds, and no or small effects were obtained for more hydrophilic volatiles. 14 The opposite was found by van Ruth et al, 15 who showed in static as well as in dynamic measurements that increased droplet diameters resulted in significantly higher release rates for many aroma compounds, which was also concluded from mathematical modelling results of flavour release from emulsions. 30 Although eight of 13 volatiles showed slightly higher release from emulsions with smaller droplets (Table 4), the effect of oil droplet size on the initial dynamic flavour release under simulated in-mouth conditions 26 was insignificant (ANOVA, p < 0.05).…”
Section: Effect Of Droplet Diametersmentioning
confidence: 94%
See 1 more Smart Citation
“…Vegetable oils play important role in human life, including contributions of essential nutrients, energy, mouth-fell, flavor, palatability, emulsifying, and complex characteristics to food products [1][2][3]. Vegetable oils are obtained from beans or seeds by pressing and/or by solvent extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Nonionic emulsifiers, such as Tweens, or surfactants based on MAG and DAG did not serve as barriers at the oil interface nor as solubilizers in terms of micelles (4)(5)(6). On the other hand, the oil fraction of an oil/water emulsion had a considerable influence on the partitioning of flavors, which in turn determined their static and dynamic release (7)(8)(9)(10)(11)(12)(13). These processes depend on the polarity of the volatiles and are governed by Nernst's law of partitioning (6,13).…”
mentioning
confidence: 99%